Rancang Bangun Aplikasi Pengelolaan Surat Masuk Dan Surat Keluar Pada PT. Petrokimia Gresik - Muhammad Daud Restu Pengeran; endra rahmawati; puspita kartika sari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
In case studies conducted at PT. Petrokimia Gresik management and recording of process incoming and process outgoing mail is still done manually, the according to results of new discussions with an the parties concerned, current management often raises several of problems have including frequent is occurrence of officers not knowing the new existence of letter documents if certain parties need information on good letters it's an incoming or outgoing letter. The letter of disposition process that is still manually using paper and the new process of filing and distributing letters must be printed repeatedly. Therefore, it requires an process incoming or outgoing mail management application that has a mail search in feature, letter of recorded and letter of disposition to get effective and efficient results. As for application users are secretaries, managers and employees.The application was built and designed with web-based, in order to quickly connect between managers, secretaries and employees at PT. Petrokimia Gresik. reports generated include incoming letter reports each period, outgoing letter reports each period, letter disposition reports each period, reports on the number of approvals or rejection of dispositions of incoming letters each period, and reports on the number of approval or rejection of outgoing letters.